Modern Concepts About Schizophrenia (Eurasian Medical Research Periodical, 2023)
This report is devoted to the problem of the etiopathogenesis of schizophrenia and the possibilities of using cognitive - behavioral psychotherapy (CBT) when working with patients with schizophrenia spectrum. The paper provides a brief overview of modern ideas about the role of biological and psychological factors in the development and recurrence of schizophrenia, emphasizes the relationship between stress and the development or exacerbation of psychosis, as well as the significance of the influence of personal characteristics, expectations, attitudes and beliefs of patients on the dynamics of the disease and the effectiveness of treatment. . The relevance of the use of psychotherapy in addition to biological methods of treatment of schizophrenia and the possibility of using cognitive - behavioral psychotherapy to work with a wide range of psychological problems in patients are substantiated. There is evidence that CPT can significantly reduce the level of stress in the lives of patients with schizophrenia, reduce the risk of relapse and the severity of painful symptoms